Peran Gembala dalam Membentuk Karakter dan Iman Kristen pada Jemaat dalam Melawan Pengaruh LGBT (Lesbian, Gay, Bisexual, dan Transgender) - Gabriel A. P. Saragih; Naomi Wahyuni; Afriani Damaris Purba (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The role of the pastor is very important and has a big impact in shaping the character and Christian faith based on biblical truth. Many challenges arise that fade the value of Christianity today, one of which is LGBT, LGBT eats away from young to old and is no exception. The purpose of this study is to provide answers to the problems of Christianity in the face of LGBT threats, namely through character building and Christian faith that is true and based on the Bible. The method used in this research is a qualitative method, data collection is done through searching and selecting relevant articles from various scientific sources. The result of this research is to know the magnitude and impact of the Shepherd in building character and Christian Faith. Through appropriate strategies the formation of character and Christian Faith can be well formed.